2017
DOI: 10.3389/fpls.2017.00412
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering Genomic Regions for High Grain Iron and Zinc Content Using Association Mapping in Pearl Millet

Abstract: Micronutrient malnutrition, especially deficiency of two mineral elements, iron [Fe] and zinc [Zn] in the developing world needs urgent attention. Pearl millet is one of the best crops with many nutritional properties and is accessible to the poor. We report findings of the first attempt to mine favorable alleles for grain iron and zinc content through association mapping in pearl millet. An association mapping panel of 130 diverse lines was evaluated at Delhi, Jodhpur and Dharwad, representing all the three p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

4
5

Authors

Journals

citations
Cited by 85 publications
(56 citation statements)
references
References 65 publications
(111 reference statements)
7
49
0
Order By: Relevance
“…It is highly resilient to diverse climate conditions and is cultivated in marginal environments of arid and semi-arid tropics of sub-Saharan Africa and Asia (Ramya et al 2018). It shows a higher degree of tolerance to severe drought, heat stress and high temperature (Anuradha et al 2017;Govindaraj et al 2018). Pearl millet grains are the rich source of the several macro-and micro-nutrients (like iron, zinc, phosphorus, and magnesium), high fiber content, αamylose, metabolizable energy, proteins, essential amino acids, thus ensuring food and nutritional security (Nambiar et al 2011;Kumar et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It is highly resilient to diverse climate conditions and is cultivated in marginal environments of arid and semi-arid tropics of sub-Saharan Africa and Asia (Ramya et al 2018). It shows a higher degree of tolerance to severe drought, heat stress and high temperature (Anuradha et al 2017;Govindaraj et al 2018). Pearl millet grains are the rich source of the several macro-and micro-nutrients (like iron, zinc, phosphorus, and magnesium), high fiber content, αamylose, metabolizable energy, proteins, essential amino acids, thus ensuring food and nutritional security (Nambiar et al 2011;Kumar et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Association studies reveal that Xibmsp11/AP6.1, an SNP marker on an acetyl CoA carboxylase gene, is strongly associated with GY, GHI (grain harvest index), and PY (panicle yield) under both treatments; whereas InDel markers viz., Xibmcp09/AP10.1 & Xibmcp09/AP10.2 of a chlorophyll a/b binding protein gene are associated with GY and stay-green traits. Using association mapping, key alleles for grain iron and zinc were demonstrated by Anuradha et al (2017). Developing MTAs (Marker Trait Associations) between 250 SSR and 17 genic markers with grain iron and zinc content for 130 diversified lines across different environs revealed that the Xicmp3092 marker had a strong association with grain iron content on LG 7, and markers Xpsmp2086 & Xpsmp2213 and Xipes0224 showed association with grain zinc content on LG 4 and LG 6, respectively; conserved association for grain iron and zinc, however, was exhibited by Xipes0180, Xpsmp2261, and Xipes0096 on LG 3, LG 5, and LG 7, respectively.…”
Section: Case Studies For Gwas In Pearl Milletmentioning
confidence: 99%
“…This climate variability is expected to increase crop vulnerability in different agro-ecologies with drastic consequences on food security and economic growth. Pearl millet is a climate-smart crop with nutritious grains (Anuradha et al 2017) and ideal for environments prone to drought and extreme heat, thereby reinforcing the fight against food insecurity in the arid and semiarid environments (Bailey et al 1979;Buerkert et al 2001;Jukanti et al 2016).…”
Section: Global Warming and Climate Changementioning
confidence: 99%